HUBUNGAN SOSIAL EKONOMI TERHADAP KEMISKINAN DI KECAMATAN ULIM DAN MEURAH DUA - Ferayanti -; Cut Risya Varlitya (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
Poverty can cause the difficulties for population in meeting their basic needs. This study aims to examine the relationship between socio-economic variables to poverty in Ulim and Meurah Dua sub-districts which are the poorest sub-districts in Pidie Jaya District. The research method used is a qualitative approach analysis based on secondary and primary data. The result shows that the economic condition of the population in Ulim and Muara Dua sub-districts is closely related to economic condition in Pidie Jaya District.